Undang-Undang Nomor 30 Tahun 2009 Tentang Ketenagalistrikan dalam Perspektif Hukum Ekonomi Islam - Anis Mahmudah (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
Islam viewed electricity as part of public ownership, ideally controlled by the state. The word "controlled" was still a dilemma because it would affect government policies in the electricity supply business. PT. PLN (Persero), as a BUMN, was given the authority to provide electricity services to the public. In implementing its functions, PT PLN (Persero) did not escape obstacles and problems. Hence, the private sector could participate in the electricity supply business. In this discourse on electricity, the research focused on how to apply Articles 4, 10, and 11 in Law No. 30 of 2009 concerning Electricity under the Perspective of Islamic Economic Law. The research design was library research using a normative approach. The source of data in this research was Law No. 30 of 2009 on Electricity and several other sources. The research method used was descriptive analysis. The research results revealed that Islam viewed electricity as public ownership that must be controlled and managed by the state for the benefit of its people. The government's policy of allowing the private sector to participate in the electricity supply business already contained elements of maslahah and was based on the rules of Taṣarruf al-Imam ‘ala Al-Ra’iyyah Manuṭun bi Al-Maṣlahah, as long as under state control. In a sense, the government still controls the involvement of the private sector, both in terms of business areas, business permits, and electricity tariffs sold to the public.